Translasi, Adaptasi dan Validasi Skala Intolerance of Uncertainty Short Version 12-item (IUS-12) ke Bahasa Indonesia - Istiqomah, Alifah Nur; Helmi, Avin Fadilla; Widhiarso, Wahyu (Universitas Islam Indonesia, 2022)
The COVID-19 pandemic has pushed people to experience the situasion of volatility, uncertainty, complexity, and ambiguity (VUCA) which has the potential to cause various mental health problems. Research on Intolerance of Uncertainty (IU) is immportant because of its crucial role as a risk factor for mental health disorders. Unfortunately, the measuring tool for that cognitive function has not yet been adapted into Indonesian culture and language. This Study aims to adapt the 12-item Intolerance of Uncertainty Scale (IUS-12) to Indonesia and determine the psychometric properties of the scale.